ECONOMIC AND MATHEMATICAL MODEL OF PREDICTION OF DEVIATION IN MOSCOW SUBURBAN RAILWAY COMPLEX - Dmitry I. Valdman (Статистика и экономика, 2016)
The article deals with the theoretical aspects of mathematical modeling and forecasting. Additionally, it describes a mathematical model for forecasting the number of incidents, depending on the number of different types of planned works with one and the same subject in service facilities, validation of the model via substituting of the data and comparing the predicted values calculated by the model and the actual values for the same periods.